Emerging Importance of Helicases in Plant Stress Tolerance: Characterization of Oryza sativa Repair Helicase XPB2 Promoter and Its Functional Validation in Tobacco under Multiple Stresses - Raikwar, Shailendra; Srivastava, Vineet K.; Gill, Sarvajeet S.; Tuteja, Renu; Tuteja, Narendra (Frontiers in Plant Science, 2015)
Genetic material always remains at the risk of spontaneous or induced damage which challenges the normal functioning of DNA molecule, thus, DNA repair is vital to protect the organisms against genetic damage. DNA hHelicases, the unique molecular motors, are emerged as potentialprospective molecules to engineer stress tolerance in plants and are involved in a variety of DNA nucleic acid metabolismc processes including DNA repair. The DNA repair helicase, OsXPB2 is an evolutionary conserved protein present in different organisms, including plants. Availability of few efficient promoters for gene expression in plants provoked us to study the promoter of XPB for better understanding of gene regulation under stress The analysis of promoter sequence from plant genome is important in understanding the gene regulation. Hereconditions. Here, we report the in silico analysis of novel stress inducible promoter of rice Oryza sativa OsXPB2 (OsXPB2). gene is reported. The in vivo validation of functionality/activity of novel stress inducible promoter of rice OsXPB2 gene promoter under abiotic and hormonal stress conditions was performed by Agrobacterium-mediated transient assay in tobacco leaves using OsXPB2::GUS chimeric construct. Our resultsThe present research revealed that OsXPB2 promoter contains cis-elements accounting for various abiotic stresses (salt, dehydration or cold) and hormone (Auxin, ABA or MeJA) induced GUS expression/activity in the promoter-reporter assay. The promoter region of OsXPB2 contains CACG, GTAACG, CACGTG, CGTCA CCGCCGCGCT cis acting-elements which are reported to be salt, dehydration, cold, MeJA or ABA responsive, respectively. Functional analysis was done by Agrobacterium-transient assays using agroinfiltration in tobacco leaves, followed by GUS staining and fluorescence quantitative analyses. The results revealed high induction of GUS activity under multiple abiotic stresses as compared to mock treated control. The present findings suggest that OsXPB2 promoter is a multi-stress inducible promoter and has potential applications in sustainable crop production under abiotic stresses by regulating desirable patterns of gene expression.